"A Lot of Students Are Already There": Repositioning Language-Minoritized Students as "Writers in Residence" in English Classrooms. (January 2022) - Seltzer, Kate
This article centers on Faith, a Latinx bilingual student who, because of her failure to pass a standardized exam in English language arts, had to repeat 11th-grade English. Despite this stigma of being a "repeater, " during the year-long ethnographic study I conducted in her classroom, Faith proved to be an insightful and critical reader and self-described poet who shared her writing with her peers as well as with other poets in online forums. Drawing from that more expansive classroom study, this article features Faith's metacommentary on language and her own writing process and explores how her insights (1) disrupt monoglossic, raciolinguistic ideologies by highlighting the disconnect between her sophisticated understandings of language and the writing process and her status as a "struggling" student; (2) draw attention her wayfinding, which chronicles her navigation of those ideologies that complicate her search for a writerly identity and obscure the translingual nature of all texts and all writers; and (3) can move teachers and researchers of writing to reimagine the writing classroom so that it (re)positions students like Faith as "writers in residence, " whose existing translingual writing practices and wayfinding can serve as mentors and guides for others.